IDENTIFIKASI TIPE DAN KELIMPAHAN MIKROPLASTIK PADA IKAN NILA (Oreochromis niloticus) DI WADUK LAHOR KABUPATEN MALANG JAWA TIMUR - Anggie Eka Wienardy; Fitriyah Fitriyah; Umaiyatus Syarifah (Binar – Biology Natural Resources Journal, 2023)
Plastics can be degraded into microplastics and easily to dispersed in waters, including reservoirs as water damming locations. Lahor Reservoir is known to be used as a location for aquaculture, one of which is nile tilapia (Oreochromis niloticus) and is fed by the Lekso river, Lahor river, and Dewi river. This certainly increases the potential for microplastic contamination and has a negative impact on aquatic biota and humans. The purpose of this study was to determine the potential for microplastic contamination in the digestive tract of nile tilapia in Lahor Reservoir, Malang Regency, East Java. The study was conducted at 4 sampling stations including Lekso river inlet, Lahor river inlet and Dewi river, Residential area of Karangkates village, and Lahor Tourism Park. 5 Fishes samples were taken at each station and the repetition process was carried out 3 times. Sample preparation with 20 ml of 30% HzO2 solution and 20 ml of 10% KOH. Identification types and abundance of microplastics was carried out with a 40× magnification stereo microscope. The results showed the discovery of several types of microplastics which is fiber, filament, fragment, and film and the highest total abundance value of microplastics was found in the Lahor river inlet and Dewi river at 6.47 particles / individual.